The clinical evaluation of Vi-one chlorhexidine mouthwash on plaque-induced gingivitis: A double-blind randomized clinical trial - Babak Amoian; Marzyeh Omidbakhsh; Soraya Khafri (Electronic Physician, 2017)
Background: Chlorhexidine (CHX) is the most effective antiseptic mouthwash to date. Essential oil such as thymol, have inhibitory and biocidal effects a range of bacteria. Objective: To determine the effect of mouthwash containing CHX and thymol on plaque induced gingivitis. Methods: This double-blind randomized clinical trial study was performed on 60 patients with plaque induced gingivitis who were randomly divided into two groups: Group I (CHX/thymol mouthwash-Vi-one) and Group II (CHX mouthwash-Behsa). Patients in each group underwent scaling and root planning and polishing, then were educated about BASS-Method brushing, and were recommended Oral-B toothbrushes and Pooneh toothpaste. The two groups were asked to rinse their mouths for 60 seconds twice a day, once in the morning and once at night, after brushing their teeth. Plaque index, gingival index, bleeding index and stain index were evaluated at baseline and 14 days later in Ramfjord teeth. Data analysis was conducted using SPSS version 21. Independent- samples t-test and paired-samples t-test were used for data analysis. Results: The results showed that plaque index and gingival index significantly reduced in two groups (p<0.001). However, group I was significantly more efficient than group II (p<0.001, p=0.021 respectively). Similar results were observed in terms of bleeding index with the difference that the two groups did not differ significantly from each other (p=0.879). Both groups significantly increased the stain index. No remarkable difference was also observed between the two groups (p=0.754). Conclusion: Based on the results of this study, we can conclude that the CHX/thymol mouthwash can be offered to patients with dental plaque-induced gingivitis, because it appears to be more effective in controlling dental plaque and gingivitis. Trial registration: The trial was registered at the Iranian Registry of Clinical Trials (http://www.irct.ir) with the Irct ID: IRCT201602231760N45. Funding: This study was part of a thesis and research project (Grant No: 9440921) supported and funded by Babol University of Medical Sciences. The authors received no financial support from Behsa pharmaceutical company (Behsa mouthwash manufacturer) or Rojin cosmetic laboratory (Vi-one mouthwash manufacturer) for this study